Using consecutive prescribed fires to reduce shrub encroachment in grassland by increasing shrub mortality. Issue 4 (1st March 2020) - Hopkinson, Peter; Hammond, Michele; Bartolome, James W.; Macaulay, Luke
Abstract : Woody plant encroachment into open grasslands occurs worldwide and causes multiple ecological and management impacts. Prescribed fire could be used to conserve grassland habitat but often has limited efficacy because many woody plants resprout after fire and rapidly reestablish abundance. If fire‐induced mortality could be increased, prescribed fire would be a more effective management tool. In California's central coast, shrub encroachment, especially of Baccharis pilularis (coyote brush), is converting coastal prairie into shrub‐dominated communities, with a consequent loss of native herbaceous species and open grassland habitat. B. pilularis has not been successfully controlled with single prescribed fire events because the shrub resprouts and reestablishes cover within a few years. We investigated whether two consecutive annual burns would control B. pilularis by killing resprouting shrubs, without reducing native herbaceous species or encouraging invasive plants. As expected, resprouting did occur; however, 2 years after the second burn, B. pilularis cover on burned plots was only 41% of the cover on unburned plots. Mortality of B. pilularis more than doubled following the second burn, likely maintaining a reduction in B. pilularis cover for longer than a single burn would have. Three native coastal prairie perennial grasses did not appear to be adversely affected by the two burns, nor did the burns result in increased cover of invasive species. Managers wanting to restore coastal prairie following B. pilularis encroachment should consider two consecutive annual burns, especially if moderate fire intensity is achievable.